Schön shown the door [electronics research investigation]. - Hellemans, A.
When charges surfaced earlier this year that work published by Lucent Bell Labs researcher Jan Hendrik Schön might be seriously flawed, the general hope and perhaps even expectation was that defects would prove minor or incidental and could be attributed to mere carelessness or overzealousness. With the release at the end of September of a blue-ribbon investigative report, all such hopes have been completely dashed; the investigation of the star Bell Labs researcher stops just short of declaring his work bogus.
Keywords: Lucent Bell Labs; Electronics research; Fraud; Jan Hendrik Scho¨n.